Market Entry Strategy for Selected Company - Poptcov, Maksim; Král, Petr, 1979-; Vokáč, Matěj; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2020)
The objective of this thesis is to develop a marketing strategy for the coffee shop to enter one of the European markets. The object of study is the Double B coffee house, which is already operating in other countries. The thesis consists of two parts, which are theoretical and practical. The theoretical part describes the knowledge associated with the coffee market in the world, services in emerging markets, appropriate entry modes, and limitations of companies from this kind of market. In the practical part, the author conducted a comparative analysis of German and British markets attractive for Double B coffee house and developed the marketing plan for entering the German market that was chosen by the author. The marketing plan contains the mode of entry, marketing goals, business model, organizational plan, communication mix, and financial plan. The theoretical and methodological basis of this thesis was extensive research of works of European and Russian specialists, analytical materials and statistical data, books, Double B data, information resources on the Internet as well as the author’s survey and interview.
Vedoucí práce: Petr Král
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses